Determinants of Financial Accounting Standards Implementation in Malaysian Commercial Banks: The Mediating Role of Internal Control Systems - Irmayanti Irmayanti; Sakinah Saharuna (Pascasarjana STIE Amkop Makassar, 2026)
The implementation of Financial Accounting Standards (FAS) is essential for ensuring transparency and reliability of financial reporting in the banking sector. This study examines the determinants of FAS implementation in Malaysian commercial banks by focusing on key organizational and regulatory factors, namely management commitment, accounting staff competency, and regulatory pressure. Internal control systems are incorporated as a mediating variable to explain how these factors influence the effectiveness of accounting standards implementation.Using a quantitative approach, data were collected through a structured questionnaire administered to accounting and finance professionals in Malaysian commercial banks. Structural Equation Modeling (SEM) was employed to analyze the relationships among variables. The results show that management commitment, accounting staff competency, and regulatory pressure have significant positive effects on FAS implementation, while internal control systems partially mediate these relationships. These findings contribute to the accounting and banking literature by emphasizing the importance of the implementation process rather than mere adoption of accounting standards and provide practical implications for regulators and bank management in strengthening governance, professional capacity, and internal control mechanisms.Keywords: Financial accounting standards; internal control systems; management commitment; regulatory pressure; Malaysian commercial banks.